A relook at visual privacy: definition and factors influencing Muslim visual privacy (MVP) - Abd Manaf, Azhani; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita (Universiti Putra Malaysia, 2019)
Past literature has indicated a lack of visual privacy in the design of terrace housing in Malaysia, especially for Malay Muslim families, owing to specific Islamic regulations and principles governing the modesty of self, family, and house. The main objectives of this paper are to analyse the definition of visual privacy from Islamic perspective or Muslim visual privacy (MVP), and to determine the factors that influence its perception among Malay Muslim communities who are living in terrace housing development in the Klang Valley, Malaysia. The study involved a survey interview of 441 respondents and 10 case studies. Findings indicate that in adapting to the contemporary urban environment of today’s terraced housing, Malay Muslim families are shifting away from the traditional Malay as well as previous Islamic concept of visual privacy. Analysis indicated that the Malay Muslim families required a balance between visual exposure and visual access in order to achieve an optimum level of visual privacy to enhance daily comforts, while still being informed by Malay culture and Islam. It is the balance between visual exposure and visual access which influences the four identified factors influencing Muslim visual privacy which are protection of aurat, security, community interaction and hospitality to guest